Caracterização de Latossolos de Mares de Morros Florestados- MG como subsídio para o entendimento da evolução dos compartimentos geomorfológicos Belo Horizonte 2019 - Brunno Cesar Pereira (2019)
The objective of this work was to analyze the evolutionary degree of two geomorphic units, based on the soil-landscape relation, from the comparison between the top Oxisols of different altimetric positions, in the region of Serra de São Geraldo, located in the mesoregion of Zona da Mata de Minas Gerais. In order to analyze the geomorphic surfaces with respect to their evolution, profiles of Oxisols present at the top of each surface were selected. Each profile was morphologically characterized in the field, as well as a description of the collection areas. Afterwards, samples of the Bw horizons of each profile were sent to the laboratory for physical, chemical, mineralogical and micromorphological analyzes. The information of the laboratory analyzes was fundamental to measure the evolution of the Oxisols and description of the relative chronology of the surfaces. For the physical analyzes, the soils located at the highest level presented higher clay content, and total silt, silt and lower silt/clay ratio, presenting a very clayey texture. The soils of the lower surface obtained reduction of the clay contents and increase of the total sand, silt and silt/clay ratio, obtaining a clayey texture. For the chemical analyzes, the electrical conductivity in water was lower for the soils of the higher surface, which indicates less amount of conducting components, like the salts, by loss by the exposure to the time. Negative ΔpH was predominant for lower soils, indicating less evolved soils, besides the sulfuric attack that indicated higher levels of iron, aluminum and titanium oxides for the Oxisols of the upper plateau, and higher Ki and Kr molecular relationships on the surface lowered. As for mineralogical analyzes, there is a predominance of gibbsite at the upper level for clay content, indicating more evolved soils, besides ilmenite, which is composed of natural iron oxides and titanium, in the sand content for the same soils. Oxisols at the lower level presented mica minerals in the sand content, indicating a lower degree of evolution. And finally, the micromorphological analysis provided relevant information regarding the matrix background distribution, showing a more homogeneous micromass, a higher occurrence and proportion for profile 1 and a larger amount of the thick material for profile 5, corroborating with higher clay content for the first profile, micromass is composed of basically clay, and total sand for profile 5, the skeleton being composed of the thick material, indicating a higher evolutionary degree for profile 1 in relation to profile 5. Therefore, the parameters used to analyze the evolutionary degree of the soils, consequently the chronology of the surfaces of the study area, showed results that corroborate with the hypothesis that the upper surface is older, with Oxisols more evolved in relation to the inferior surface, than presented Oxisols with a lower degree of evolution.